2017
DOI: 10.4103/aer.aer_91_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrathecal clonidine and fentanyl as adjuvant to hyperbaric bupivacaine in subarachnoid block for lower limb orthopedic surgery

Abstract: Background:Many studies are there using adjuvants such as clonidine and fentanyl with bupivacaine in the subarachnoid block for prolonging postoperative analgesia. However, literature is divided regarding the dosage and efficacy of both intrathecal adjuvants. Furthermore, these adjuvants have their own side effects. Hence, search for ideal intrathecal adjuvant between clonidine and fentanyl to bupivacaine goes on.Aim:The aim of the present study was to compare the effect of intrathecal clonidine and fentanyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
2
14
0
1
Order By: Relevance
“…One group (group C) received intra-thecal hyperbaric bupivacaine (2.5 ml) and 50 μg clonidine (diluted to 0.5 ml) while other group (group F) received intra-thecal hyperbaric bupivacaine (2.5 ml) and fentanyl 25 μg (diluted to 0.5 ml). They found out that duration of sensory and motor block was significantly prolonged in Group C compared to Group F [9].…”
Section: Discussionmentioning
confidence: 95%
“…One group (group C) received intra-thecal hyperbaric bupivacaine (2.5 ml) and 50 μg clonidine (diluted to 0.5 ml) while other group (group F) received intra-thecal hyperbaric bupivacaine (2.5 ml) and fentanyl 25 μg (diluted to 0.5 ml). They found out that duration of sensory and motor block was significantly prolonged in Group C compared to Group F [9].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, there was no significant difference in heart rate and MAP between the groups. The vital signs showed no significant changes in previous studies by adding fentanyl, midazolam, or clonidine to bupivacaine to our journey 1,15,19 . One of the limitations of this study was the type of orthopedic injury severity in patients was not the same and this could be effective at the onset of the patient's pain and distort the results.…”
Section: Discussionmentioning
confidence: 51%
“…They used 20 µg of fentanyl and 2 mg of midazolam, which could not account for the difference in the results of the two studies 3 .Routray et al also reported that adding clonidine to fentanyl in the intrathecal anesthesia could increase the duration of post-operative analgesia. Although the type of medications used in these two studies was completely different, it was concluded that the addition of another drug to fentanyl could enhance its effects and even be useful in controlling post-operative pain 15 .Singh et al also compared the addition of two different doses of fentanyl, and clonidine to bupivacaine, in intrathecal anesthesia and reported that both doses could reduce the duration of anesthesia better than that of the control group, and increases the duration of sensory nerve block, motor block, and analgesia following surgery 16 . Moreover, Tucker et al used a combination of 2 mg of midazolam and 10 µg of fentanyl to control labor pain and reported that the given method could more effectively control pain.…”
Section: Discussionmentioning
confidence: 99%
“…Juitaet al, [13] also reported a significantly prolonged anaesthesia time with bromage score 2 for clonidine groups compared to sufentanil groups in gynaecological surgery. Routray et al, [14] had also reported a increased duration of motor block in clonidine group as compared to fentanyl group when administerd intrathecallywith hyperbaric bupivacaine in lower limb orthopaedic surgeries. The fact that present study demonstrates the motor block enhancing effect of clonidine in doses as low as 30μg is also of importance as a majority of earlier studies have showed this effect only at doses greater than 50μg; therefore it is important to realize that even low doses of intrathecal clonidine can cause a undesirably high motor block.…”
Section: Discussionmentioning
confidence: 95%